Improving the compulsory land acquisition procedure: interpreting the land acquisition (amendment) act 2016 (act a1517) / Asma Senawi…[et al.] - Senawi, Asma; Ahmad@Mohamed, Nurulanis; Mat Zan, Rubiah (Universiti Teknologi MARA, Kedah, 2018)
The compulsory land acquisition is the process by which the government acquires the private land which needed for any public purpose or for a purpose beneficial to the economic development of Malaysia. The provisions relating to land acquisition are stipulated under the Land Acquisition Act 1960 (“the Acquisition Act”). Some 19 years after the last round of amendments to the Acquisition Act, the Land Acquisition (Amendment) Act 2016 (“the Amendment Act 2016”) had been introduced. The Natural Resources and Environment Minister has said that changes to the Acquisition Act are necessary especially for infrastructure development to retain the country’s competitiveness in heading towards a developed nation. This paper aims to examine the changes in the Amendment Act 2016 as to summarize the reason for the amendment. The authors using content analysis to identify the changes involved in the Amendment Act 2016. The study reports the reason for the amendment is to explain and improve the implementation procedure in the acquisition of underground land, strata property and temporary occupation or use of land beside to explain and improve the procedure concerning the reference to court by the landlord. In addition, the amendment is to streamline the existing provisions to meets the current requirement. The findings, therefore, can be referred to all the key players in land acquisition procedure and as an initiation to assess the effectiveness of the Amendment Act 2016.